ESTABLISHMENT OF A STUDENT'S CULTURE OF DISCIPLINE THROUGH THE IMPLEMENTATION OF THE SCOUTING HONOR CODE IN ELEMENTARY SCHOOLS - Utami, Fadilla Diah Winta; Malaikosa, Yes Matheos Lasarus; Supriyanto , Djoko Hari (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This study aims to determine how the formation of a disciplined culture of students through the practice of the scout honor code at SDN Tambakromo 1, Geneng District. The research subjects were 1 scout extracurricular coach, 1 school principal, and 26 scout raiser members consisting of 10 male students and 16 female students. Data collection techniques are using observation and interviews. The data were analyzed using data reduction, data presentation and conclusion drawing. The results of this study indicate that the formation of a culture of discipline carried out at SDN Tambakromo 1 through the practice of the scout honor code has been going well. The efforts made by coaches and schools in establishing a culture of discipline at SDN Tambakromo 1, namely: 1) Practicing the honor code of the scout movement. The Scout honor code for the raising group consists of a promise called Trisatya and a moral provision called Dasadarma; 2) Learning by doing; 3) Interesting and challenging outdoor activities; 4) Team system; 5) Partnership with adult members of each activity; 6) separate unit system for boys and girls.